The occurrence of the Lessepsian migrant Lutjanus argentimaculatus in the Mediterranean, (Actinopterygii: Perciformes: Lutjanidae) first record from the coast of Israel - Sonin, Oren (Array, 2019)
Two specimens of the Lessepsian migrant, the Mangrove red snapper Lutjanus argentimaculatus are reported from the Mediterranean coast of Israel. L. argentimaculatus was first recorded in the Mediterranean in 1979 by a single specimen. Over three decades later and only in the last two years four specimens, including the two reported herein, were recorded. This pattern strongly suggests that L. argentimaculatus has established a sustainable population in the Mediterranean.